Enhancing EFL Learner Motivation through Task Based Translanguaging Practices in Indonesian Secondary Schools - Muhammad Nasirudin; Hanifan Hamid Rifaie (Journal of Applied Linguistics and Language Practice, 2025)
This study explores how task-based translanguaging practices can enhance English as a Foreign Language (EFL) learner motivation in Indonesian secondary schools. Recognizing that learners often draw on their full linguistic repertoires, this research examines how integrating translanguaging into task-based learning fosters engagement, confidence, and communicative competence. The study employed a mixed-methods approach involving classroom observations, student questionnaires, and semi-structured interviews with teachers. Data were analyzed to identify motivational shifts and changes in learner participation across various task types. Findings indicate that translanguaging practices significantly improve learner motivation by reducing anxiety, promoting collaborative learning, and increasing comprehension. Furthermore, task-based translanguaging encourages meaningful language use and provides students with greater agency in the learning process. The results suggest that combining task-based learning with translanguaging strategies offers an effective pedagogical framework for motivating EFL learners in multilingual contexts like Indonesia. These findings have implications for curriculum design, teacher training, and classroom practices aimed at creating inclusive and dynamic EFL learning environments that acknowledge students’ linguistic and cultural resources.